Case report: A case of acute exacerbation of interstitial pneumonia associated with TAFRO syndrome - Shimada, Yoshitaka; Nagaba, Yasushi; Fujino, Mako; Okawa, Hiroyuki; Ehara, Kaori; Shishido, Eri; Okada, Shinya; Yokomori, Hiroaki (Frontiers in Medicine, 2023)
Cytokine storm caused by the overproduction of inflammatory interleukin (IL)-6 plays a central role in the development of acute inflammation. The extremely rare disease, TAFRO syndrome, progresses quickly. Renal dysfunction, fever, reticulin fibrosis, anasarca, thrombocytopenia, and organomegaly with pathological findings such as idiopathic multicentric Castleman disease are all characteristics of TAFRO syndrome. Interstitial pneumonia (IP), which is not characteristic of this disease, is probably a complication of the inflammatory process. An 88-year-old man presented with a 3-day history of fever, dry cough, and progressive dyspnea. After he was first treated with antibiotics, he was transferred to our hospital because he showed no improvement. Data showed hemoglobin Hb 90.00(SI)(9.0 g/dL); leukocyte count WBC 23 × 109/L(SI) (23 000/μL (neutrophils 87.5%, lymphocytes 2.5%, blast cells 0%)); hemoglobin 90 g/L (9.0 g/dL); platelet count 101.00 × 109/L (10 100/μL); lactate dehydrogenase 4.78 µkat/L (286 U/L); serum albumin 25.00 g/L (2.5 g/dL); blood urea nitrogen 18.17 µmol/L (50.9 mg/dL); creatinine 285.53 µmol/L (3.23 mg/dL); C-reactive protein 161.50 mg/L (16.15 mg/dL); IL-6 1830 pg/mL; and surfactant protein D level 26.6 ng/mL. Findings from computed tomography indicated increased ground-glass opacities without traction bronchiectasis consistent with acute IP. The diagnosis was leukocytosis and progressive kidney injury. After bone marrow aspiration caused by persistent pancytopenia, mild reticulin fibrosis was identified. Because of the high IL-6 concentration, which revealed small atrophic follicles with regressed germinal centers surrounded by several lymphocytes, right inguinal lymph node biopsy was performed. Two minor and three major criteria led to diagnosis of TAFRO syndrome. Administrations of antibiotic therapy and methylprednisolone pulse therapy were ineffective. After rapid progress of respiratory failure, the patient died on day 30 of hospitalization. Autopsy of lung tissues showed diffuse alveolar damage with hyaline membranes. Based on these findings, we diagnosed acute exacerbation of IP associated with TAFRO syndrome due to IL-6 overproduction-associated cytokine storm.